Oral implantation in humans of Streptococcus mutans strains with different degrees of hydrophobicity. - Svanberg, M (1984)
The more hydrophobic, rough-colony-forming, streptomycin-resistant Streptococcus mutans parent strains GW Smr and LK Smr and the less hydrophobic, smooth-colony-forming, streptomycin-resistant variant strains GW36 Smr and LK36 Smr were implanted in oral cavities. Strains GW Smr and LK Smr implanted significantly better than strains GW36 Smr and LK36 Smr. The hydrophobicity of and the colony morphology formed by the different S. mutans strains did not seem to be affected throughout the experiment.